2018
DOI: 10.1158/0008-5472.can-18-0532
|View full text |Cite
|
Sign up to set email alerts
|

CircNT5E Acts as a Sponge of miR-422a to Promote Glioblastoma Tumorigenesis

Abstract: Circular RNA and long noncoding RNA function as efficient miRNA sponges that regulate gene expression in eukaryotes. However, the sponges of functional miRNAs in glioblastoma remain largely unknown. Here, we identify a subset of circRNAs and lncRNAs that are specifically increased in miR-422a-downregulated glioblastoma tissues. We characterized a novel circRNA derived from NT5E, named circNT5E, that is regulated by ADARB2 binding to sites flanking circRNA-forming introns. We hypothesized that circNT5E may serv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
221
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(232 citation statements)
references
References 58 publications
(77 reference statements)
9
221
0
2
Order By: Relevance
“…CircNT5E controls multiple pathologic processes, including cell proliferation, migration, and invasion, by directly sponging miR-422a and inhibiting its activity. Furthermore, circNT5E was observed to sponge other miRNAs, suggesting the existence of a more complex regulatory network controlled by circNT5E in GBM [122].…”
Section: Back Splicing In Brain Tumorsmentioning
confidence: 95%
“…CircNT5E controls multiple pathologic processes, including cell proliferation, migration, and invasion, by directly sponging miR-422a and inhibiting its activity. Furthermore, circNT5E was observed to sponge other miRNAs, suggesting the existence of a more complex regulatory network controlled by circNT5E in GBM [122].…”
Section: Back Splicing In Brain Tumorsmentioning
confidence: 95%
“…18 For example, circ_0005230 was proved to be a dismal prognostic marker for breast cancer patients. 7 In this study, we found that upregulation of circ-CDC45 is related to larger tumor size and higher WHO grades. Recently, circ-CDC45 was identified enhanced in GM tissues than that in the normal tissues screened by circRNA microarray.…”
Section: Discussionmentioning
confidence: 54%
“…Some studies reported that circRNA might act as sponges for miRNA, regulating the expression of miRNA target genes in glioma. Wang R et al found that circNT5E could promote cell proliferation, migration, and invasion through acting as a sponge of miR-422a (Wang et al 2018b). Li X et al found that circ_0001946 acted as a competing endogenous RNA to modulating miR-671-5p and CDR1, and reduced proliferation, migration, invasion and increased apoptosis in GBM cells (Li and Diao 2019).…”
Section: Discussionmentioning
confidence: 99%